Sources of beach sand at creciente island, Baja California Sur, Mexico: Fourier grain-shape analysis - Murillo, JM; Osborne, RH; Gorsline, DS (Ciencias Marinas, 1994)
Fourier grain-shape analysis (FGSA) of detrital quartz grain was used to identify local sources for medium-grained (0.25 to 0.50 mm) sand in Creciente barrier island, which is located on the west coast of Baja California Sur, Mexico. A total of 52 samples from Creciente Island and vicinity were analyzed. The results of FGSA include mean values of harmonic amplitude values, which may be employed to characterize the shape composition for each sample. These values were used as for statistical procedures used to identify sand sources. Factor analysis (BMDP 4M), based on mean harmonic amplitude values for each sample, was used to identify sample groups, which, in turn, served to define the probable sources. Multivariate analysis of variance indicated how much of the shape information was explained by each factor or variable, and was also used to facilitate the sedimentologic interpretation of one factor (roughness). Levine’s F-test was used to determine whether or not the explained variance for each of the 23 shape variables (harmonics) is statistically significant. Levine’s F-test also was used to measure the difference between sample values resulting from analysis of variance. Discriminate function analysis was used to estimate the percentage of sand derived from each of the potential sources. The beach sand at Creciente Island has two primary sources. The first is the inner continental shelf, which contributed from approximately 50 to 57% of the sand in observed samples. The second source is the nearby rivers, which contributed from 43 to 50%.